Resistência à fratura de molares tratados endodonticamente restaurados com diferentes técnicas diretas - Zambiasi, Bianca Soares (2018)
Aims: To evaluate, in vitro, the fracture resistance and the pattern of failure of endodontically treated molars restored with different direct restorative techniques. Materials and methods: 70 third healthy molars extracted were divided into 7 groups (n = 10): (all groups except H received root canal treatment) H-sound; Z250PT – horizontally transfixed fiberglass post + Z250 composite resin; Z250FO – Z250 + occlusal fiberglass tape; Z250FP – Z250 + fiberglass tape along the floor of the pulp chamber; PREP-only cavity preparation; COL – Restored with Coltosol. After the restorative procedures, the samples were subjected to 250,000 cycles of mechanical testing fatigue under 200N. Right after, the samples were submitted to the fracture resistance testing and the analysis of the type of fracture which were classified as follows: Pulp chamber floor (non-repairable) or cusps (repairable). Results: (means (N) followed by the same letter do not present statistical difference to ANOVA and Tukey (p > 0.05): H 3832A; Z250PT 2726B; Z250FO 1647C; Z250FP 1548C; Z250 1622C; PREP 514D; COL 450D. Conclusion: The restorative technique that presents higher resistance to the fracture as well as higher percentage of repairable failures is horizontal transfixing with fiberglass post, Z250PT group. The insertion of fiberglass tape into the composite resin did not present improvement in the resistance, nor in the fracture pattern, when compared to the use of traditional composite resin.